MENJAGA KEHORMATAN SEBAGAI PERLINDUNGAN NASAB PERSPEKTIF MAQASHID SYARI’AH - M. Lutfi Khakim; Mukhlis Ardiyanto (Nizham Jurnal Studi Keislaman, 2020)
Allah created humans with perfect and honorable nature from other creatures. But the honor that is bestowed must be guarded with respectable behavior. both household building honor or personal respect need to be maintained for the creation of quality offspring in accordance with the concept of maqashid asy-shari'ah, one of which is to maintain nasab hifdz nasl. Today guarding the respect of the offspring both in terms of concept or practice, began to be eroded by freedom and Westernization. This study uses library research library research methods, the data used are secondary data that is data obtained by studying library materials in the form of books, documents, regulations, research results, archives and as related to the problems in question. researched. The results of this study indicate that Islam is very careful in maintaining the nasab and honor of each adherent. And do not recommend to damage the honor and one's descendants. All forms of behavior that damage honor and offspring are strictly forbidden and even Islam is firm in providing sanctions for violators.